English Philology Students’ Opinions on their L2 Pronunciation Skills: A Changing Perspective - Dorota Lipinska (Yayasan Visi Intan Permata, 2017)
The aim of this paper is to present the results of a longitudinal study based on anonymous (encoded) questionnaires filled in by a group of students enrolled at a university English Studies programme. The questionnaires analysed the students’ views and opinions concerning their own pronunciation in English as an L2.The initial stage of the study took place at the beginning of the first semester of studies before the first pronunciation class in which the students took part. Then the study participants were trained in both segmental and suprasegmental phonetics of English. Finally, they filled in almost the same questionnaire. The obtained results have shown that although initially the subjects had been satisfied with their own L2 pronunciation, later they realized that it had left a lot to be desired and it improved only after the university course in English phonetics.